Psychotria apdavisiana sp. nov. (Rubiaceae), a remarkable calciphile from the southern karst of Papua New Guinea - Takeuchi, Wayne (Phytotaxa, 2013)
Psychotria apdavisiana is described from remote environments in Papua New Guinea’s Southern Escarpment. The calciphilous species is the latest addition to an expanding conspectus of discoveries from the limestone biome.